Remembering Constantine at the Milvian Bridge - Van Dam, Raymond (Cambridge Univ. Press, 2011)
"Constantine was the first Christian emperor in the Roman empire. Before his victory in 312 at the battle of the Milvian Bridge outside Rome, he claimed to have seen a vision of a cross in the sky. The book analyzes the legends about the battle and the vision, from the later Roman empire to the later medieval period. By rehabilitating the significance of Maxentius, the losing emperor, this book also emphasizes the competing ideas at stake about Roman emperorship, the contours of the empire,and the place of Rome"--